2022
DOI: 10.1186/s12986-022-00720-1
|View full text |Cite
|
Sign up to set email alerts
|

Association between surrogate indicators of insulin resistance and risk of type 2 diabetes combined with hypertension among Chinese adults: two independent cohort studies

Abstract: Background Type 2 diabetes (T2D) combined with hypertension has a higher risk of developing cardiovascular diseases. This study aimed to investigate the relationships between the surrogate indicators of insulin resistance (TyG, TG/HDL, and Mets-IR) with the risk of T2D combined with hypertension. Methods This study is based on a functional community cohort from Beijing and the China Health and Retirement Longitudinal Study, comprising 4234 and 4658… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…Our mediation analyses showed TyG index playing a key role in the association of CVAI with HTN-DM comorbidity. Similar to our results, a study by Dong et al also reported TyG index mediating the association between BMI/WC and HTN-DM comorbidity (30). In addition, consistent with our findings for HTN or DM, recent studies found that the BMI-HTN or BMI-DM association was medicated by TyG index (31,32).…”
Section: Discussionsupporting
confidence: 93%
“…Our mediation analyses showed TyG index playing a key role in the association of CVAI with HTN-DM comorbidity. Similar to our results, a study by Dong et al also reported TyG index mediating the association between BMI/WC and HTN-DM comorbidity (30). In addition, consistent with our findings for HTN or DM, recent studies found that the BMI-HTN or BMI-DM association was medicated by TyG index (31,32).…”
Section: Discussionsupporting
confidence: 93%
“…Ultimately, we included a total of 22 studies involving 668,486 participants, including 12 cross-sectional studies (28-39) and 10 cohort studies (40)(41)(42)(43)(44)(45)(46)(47)(48)(49). The participants were mainly from the general population in urban or rural areas, and a few studies mentioned special occupational groups.…”
Section: Study Characteristics and Quality Evaluationmentioning
confidence: 99%
“…The study by Bala et al also showed that although there is a positive and strong relationship between the TyG-BMI index and hypertension, it is not superior to BMI and TyG index and TyG-WC [13]. In addition, several cross-sectional studies have introduced the TyG-BMI index as an accurate surrogate for IR to predict the risk of hypertension [13,15,27,28]. In general, the results of similar studies indicate a strong relationship between high the TyG-BMI and risk of hypertension, but the accuracy and power of prediction of TyG-BMI index for the early diagnosis of hypertension require more studies in different populations.…”
Section: Discussionmentioning
confidence: 99%
“…According to the limitation of IR measurement, its alternative indicators are usually used. One of the most complete surrogate indices of IR is the glucose-triglyceride body mass index (TyG-BMI), which is a combination of triglyceride, glucose, and BMI [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%